Antibacterial Activity of Lactobacillus acidophilus Strains Isolated from Honey Marketed in Malaysia against Selected Multiple Antibiotic Resistant (MAR) Gram-Positive Bacteria - Aween, MM; Hassan, Z; Muhialdin, BJ; Eljamel, YA; Al-Mabrok, ASW; Lani, MN (Wiley, 2024)
Indexed by SCOPUS